Landscape Design Of The Rudang Mayang Natural Bathing Area In Langkat District Using An Ecological Approach - Ruth Novita Sari Siagian; Ramayana Bachtiar; Fariz Harindra Syam (CV. AFDIFAL MAJU BERKAH, 2024)
Currently, the development of tourist attractions in Indonesia is increasing, both cultural tourism and natural tourism. Designing a tourist area is very important because it is basically an effort to develop and utilize the potential to increase the attraction of local and foreign tourists. The Rudang Mayang natural bathing area is one of the tourism potentials in Namu Ukur sub-district, Langkat Regency. However, currently the condition of the Rudang Mayang natural baths is not organized and not managed optimally, where the existing potential is not utilized effectively. The landscape design of the Rudang Mayang natural bathing area is a design that presents a new tourist area design based on the potential that exists from within and outside the area, both in terms of zoning concepts, circulation patterns, materials and other supporting facilities. Landscape ecology is a concept applied in the design of the Rudang Mayang natural bath which displays a geographical area that displays the expression of the natural landscape and the reciprocal relationships within it which have a close relationship with human activities, as well as an aesthetic level.